Nonconfinement Structure Revealed in Dion–Jacobson Type Quasi‐2D Perovskite Expedites Interlayer Charge Transport. Issue 49 (22nd October 2019) - Yu, Shuang; Yan, Yajie; Abdellah, Mohamed; Pullerits, Tõnu; Zheng, Kaibo; Liang, Ziqi
Abstract: Dion–Jacobson (DJ) type 2D perovskites with a single organic cation layer exhibit a narrower distance between two adjacent inorganic layers compared to the corresponding Ruddlesden–Popper perovskites, which facilitates interlayer charge transport. However, the internal crystal structures in 2D DJ perovskites remain elusive. Herein, in a p ‐xylylenediamine (PDMA)‐based DJ perovskite bearing bifunctional NH3 + spacer, the compression from confinement structure (inorganic layer number, n = 1, 2) to nonconfinement structure ( n > 3) with the decrease of PDMA molar ratio is unraveled. Remarkably, the nonconfined perovskite displays shorter spacing between 2D quantum wells, which results in a lower exciton binding energy and hence promotes exciton dissociation. The significantly diminishing quantum confinement promotes interlayer charge transport leading to a maximum photovoltaic efficiency of ≈11%. Additionally, the tighter interlayer packing arising from the squeezing of inorganic octahedra gives rise to enhanced ambient stability. Abstract : Nonconfinement structure is disclosed in 2D Dion–Jacobson perovskite ( p ‐xylylenediamine, PDMA)MA n −1 Pb n I3 n +1 ( n > 3), which promotes interlayer exciton splitting and charge transport, leading to an impressive power conversion efficiency (PCE) up to 11% in inverted planar solar cells with greatly enhanced stability.